Time resolved XANES illustrates a substrate-mediated redox process in Prussian blue cultural heritage materials. (May 2016) - Gervais, Claire; Lanquille, Marie-Angélique; Moretti, Giulia; Réguer, Solenn
Abstract: The pigment Prussian blue is studied in heritage science because of its capricious fading behavior under light exposure. We show here that XANES can be used to study the photosensitivity of Prussian blue heritage materials despite X-ray radiation damage. We used an original approach based on X-ray photochemistry to investigate in depth the redox process of Prussian blue when it is associated with a cellulosic substrate, as in cyanotypes and watercolors. By modifying cation and proton contents of the paper substrate, we could tune both rate and extent of Prussian blue reduction. These results demonstrate that the photoreduction and fading of Prussian blue is principally mediated by the substrate and its interaction with the oxygen of the environment.